On my own two feet : from losing my legs to learning the dance of life - Purdy, Amy; Burford, Michelle (William Morrow, an imprint of HarperCollinsPublishers, 2014)
Dancing With the Stars sensation Amy Purdy reveals the story of how losing her legs led her to find a spiritual path. When the Las Vegas native was just nineteen, she contracted bacterial meningitis and was given less than a two percent chance of survival. In a near-death experience, she saw three figures who told her: "You can come with us, or you can stay. No matter what happens in your life, it's all going to make sense in the end." In that moment, Amy chose to live.